2017
DOI: 10.5089/9781475599732.001
|View full text |Cite
|
Sign up to set email alerts
|

Debt Sustainability in Low-Income Countries: Policies, Institutions, or Shocks?

Abstract: This paper estimates the determinants of external debt distress in low-income countries (LICs), disentangling the roles of institutions, shocks, and policies. The most prominent factors in raising the risk of debt distress are the weak protection of private property rights, adverse shocks to real non-oil commodity prices, and a high debt burden. Results also suggest that weak economic institutions tend to raise the probability of debt distress through persistently weak economic policies and high vulnerability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…This is in contrast to some empirical literature, Gourinchas and Obstfeld (2012) for example, showed that public debt and output gap were statistically insignificant as debt crisis predictors. Our results however are in keeping with Gündüz (2017) and Herz and Tong (2008) findings.…”
Section: Results Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…This is in contrast to some empirical literature, Gourinchas and Obstfeld (2012) for example, showed that public debt and output gap were statistically insignificant as debt crisis predictors. Our results however are in keeping with Gündüz (2017) and Herz and Tong (2008) findings.…”
Section: Results Analysissupporting
confidence: 92%
“…Non-energy prices on the hand includes metals (31.6%), Agricultural commodities (64.9%) and Fertiliser (3.6%). No attempt is made to create country specific commodity prices in the spirit of (Bazzi and Blattman 2014), instead all commodity prices are time-specific variables as used by Gündüz (2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations